Verification of model of external population exposure in Japan after the accident at the “Fukushima-1” NPP - V. Yu. Golikov (Радиационная гигиена)
The paper is devoted to the verification of the model of external exposure of the Japanese population from radioactive fallout after the accident at the “Fukushima-1” NPP published by UNSCEAR in 2014. The paper presents specific quantitative examples of the verification of the external exposure model of the Japanese population after the accident at the “Fukushima-1” nuclear power plant. As an independent set of experimental data for validation of the model estimates we used the results of measurements of individual doses of external radiation in various population groups in Japan in different time periods after fallout. In the case of the deterministic version of the model, it was shown that for the adult population working mainly outdoors (construction workers and agricultural workers), the differences between the average values of effective doses predicted by the model and those obtained on the basis of measurements were less than 20%. For office workers, this difference was larger, from 34 to 70%, depending on whether their office buildings are wooden or multi-story concrete. For children under 16 years of age and a longer period of time for measuring individual doses after radioactive fallout (2011 – 2015), the differences between the model average effective doses and those estimated on the basis of measurements ranged from –24% to +32% in different time periods. In the case of the stochastic version of the model, it was shown that for the three considered groups of the adult population the distributions of individual doses obey the logarithmically normal law and the differences in the values of the calculated and experimental geometric means ranged from –7% to +20%. The geometric standard deviation values obtained in the simulation were always slightly higher than the similar values estimated based on the measurement results.